Reality Tv And The Promotion Of The Individualism Thesis: Mbc's Top Chef 2 As A Case Study - Rim Letaief (The Journal of Studies in Language, Culture and Society)
Format localization is one of the recent trends in media production. MBC, the most watched Arab channel, has achieved much success thanks to its adapted factual entertainment programs. Top Chef, the US-based program, has been one of MBC’s most successful reality TV productions, running for five seasons. Based on Lévi-Strauss’s binary-opposition theory, the study at hand attempts to prove that this program contributes to the promotion of the American cultural tenet of individualism. Through applying a qualitative textual analysis to the thirteen episodes of Top Chef 2, the current paper seeks to uncover the interplay between the thesis of individualism and the antithesis of collectivism in the program, revealing the conflict established between these two opposing cultural dimensions. The synthesis to the contradiction between the collectivist nature of Arabs and the individualistic narrative of the made-in-America Top Chef is reflected through valorizing individualism and encouraging the Arab chefs to embrace different Individualistic tendencies, from the quest for uniqueness to self-interest and self-reliance in order to achieve success in the program.